Effect of Educational Level, Environment and Quality of Service on Compulsory ’Personal Tax Objectives In Makassar City - Fajriani Azis (Jurnal Ad'ministrare, 2020)
Taxes are the largest source of domestic revenue which are used to finance government and development expenditures. This study aims to determine the effect of education level, taxpayer environment and service quality to personal tax payment compliance in Makassar - Indonesia. This research is a correlational characteristic of education level, taxpayer environment and quality of service of the tax office and their influence on tax- payers’ compliance at the Tax Office in Makassar. The population in this study comprises of individual taxpayers registered at the Makassar Tax Office, in the fiscal year of 2019 amounting to 100 people. The sampling is done by accidental sampling. Data collection was through observations, interviews, and documentation study. The data collected is analyzed by multiple linear regression analysis. The result of the analysis shows that education level, taxpayer environment and tax service quality have a significant effect on taxpayer compliance. However, the dominant effect is the level of education of the taxpayers. This research is expected to be useful for researchers and policy makers